AN EFFICIENT STRUCTURAL REANALYSIS MODEL FOR GENERAL DESIGN CHANGES AND BASED ON THE FLEXlBILlTY METHOD
Approximate structural retmolysis methods haw 10f’IJ/ bUff pursued in quest for ejJiclfmcy so a.t’ to enhance the" practICal applicallon in the a.utument and verification oj desIgns Jollowmg design modiji£otions. TheJe hav been a/sigmficant practical importance with particular emphasi.t on design optImIzation of/arge-scall! structural systems in which thousands of design modifications need to carned out during the search operatiOl’l to Idenllfyoptlmai S